Domestic political survival and international conflict: Is democracy good for peace? - Sandeep Baliga; David Lucca; Tomas Sjostrom (Rutgers University, Department of Economics, 2009)
We build a game-theoretic model where aggression can be triggered by domestic political concerns as well as the fear of being attacked. In the model, leaders of full and limited democracies risk losing power if they do not stand up to threats from abroad. In addition, the leader of a fully democratic country loses the support of the median voter if he attacks a non-hostile country. The result is a non-monotonic relationship between democracy and peace. Using the Polity IV dataset, we classify countries as full democracies, limited democracies, and dictatorships. For the period 1816-200, Correlates of War data suggest that limited democracies are more aggressive than other regime types, including dictatorships, and not only during periods when the political regime is changing. In particular, a dyad of limited democracies is more likely to be involved in a militarized dispute than any other dyad (including mixed dyads, where the two countries have different regime types). Thus, while full democratization might advance the cause of peace, limited democratization might advance the cause of war. We also find that as the environment becomes more hostile, fully democratic countries become more aggressive faster than other regime types.
Keywords: C7; 330; democracy; peace; Politisches System; Politischer Konflikt; Demokratie; Frieden; Public Choice; Spieltheorie